2023
DOI: 10.1111/ceo.14205
|View full text |Cite
|
Sign up to set email alerts
|

Rhegmatogenous retinal detachment surgery: A review

Abstract: Rhegmatogenous retinal detachment (RRD) is a serious surgical condition with significant ocular morbidity if not managed properly. Once untreatable, approaches to the repair of RRD have greatly evolved over the years, leading to outstanding primary surgical success rates. The management of RRD is often a topic of great debate. Scleral buckling, vitrectomy and pneumatic retinopexy have been used successfully for the treatment of RRD. Several factors may affect surgical success and dictate a surgeon's preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
5
0
2
Order By: Relevance
“…Despite promising advancements, their work mainly focused on the presence or absence of the target disease. However, the concrete localization of the RD lesions, a crucial need for therapeutic decision-making including the preoperative posture and surgical options, is not fully emphasized (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Despite promising advancements, their work mainly focused on the presence or absence of the target disease. However, the concrete localization of the RD lesions, a crucial need for therapeutic decision-making including the preoperative posture and surgical options, is not fully emphasized (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Patients often have symptoms such as fixed black shadows in front of the eyes, distortion of vision when the macula is involved, and loss of visual acuity [4][5][6] . Retinal breaks are mainly closed surgically, and for uncomplicated RRD, treatment is primarily performed by scleral buckling operation [7][8] . Scleral buckling is an extraocular procedure for RRD, and patients do not require long-term postoperative immobilization [9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this shift is the potential complications associated with vitrectomy and SB, such as cataracts, glaucoma, and vision loss [18] [19] [20]. Lens-sparing techniques aim to preserve the natural lens while treating RRD, whereas lensectomy/phaco-procedures involve removal of the natural lens and replacement with an intraocular lens (IOL) implant [21]. Studies have shown that lens-sparing techniques have comparable success rates to lensectomy/phaco-procedures, with lower rates of cataract formation and other complications [22] [23].…”
Section: Introductionmentioning
confidence: 99%